2021
DOI: 10.1111/nph.17759
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary divergence in embryo and seed coat development of U’s Triangle Brassica species illustrated by a spatiotemporal transcriptome atlas

Abstract: data for the major subcompartments of the seed, from the unfertilized ovule to the mature embryo and seed coat. This comprehensive dataset for seed development in tetraploid and ancestral diploid Brassicas provides new insights into evolutionary divergence and expression bias at the gene and subgenome levels during the domestication of these valued crop species. Comparisons of gene expression associated with regulatory networks and metabolic pathways operating in the embryo and seed coat during seed developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 84 publications
(139 reference statements)
4
15
0
Order By: Relevance
“…For embryo samples, the analysis showed a higher degree of correlation in neighboring progressive stages of embryo development ( Figure 1 B), and displayed a continuous transition of transcriptomes during embryonic development (from GE to HE to TE to CE to ME, Figure 1 A), indicating the dynamic regulation of gene expression during embryogenesis. Moreover, the sample distance analysis among different stages of embryonic development divided all embryo samples into three subgroups, including middle stage (GE and HE), late stage (TE and CE), and mature stage (ME), and this assigned grouping is consistent with previous studies from other model plants and crop species [ 17 , 19 , 30 ]. The results from all three clustering analyses reveal close similarity amongst the transcriptome datasets and support substantial conservation of gene expression during embryogenesis in flax.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…For embryo samples, the analysis showed a higher degree of correlation in neighboring progressive stages of embryo development ( Figure 1 B), and displayed a continuous transition of transcriptomes during embryonic development (from GE to HE to TE to CE to ME, Figure 1 A), indicating the dynamic regulation of gene expression during embryogenesis. Moreover, the sample distance analysis among different stages of embryonic development divided all embryo samples into three subgroups, including middle stage (GE and HE), late stage (TE and CE), and mature stage (ME), and this assigned grouping is consistent with previous studies from other model plants and crop species [ 17 , 19 , 30 ]. The results from all three clustering analyses reveal close similarity amongst the transcriptome datasets and support substantial conservation of gene expression during embryogenesis in flax.…”
Section: Resultssupporting
confidence: 84%
“…FAD3 of Arabidopsis encodes an endoplasmic reticulum localized enzyme responsible for the synthesis of 18:3 fatty acids from phospholipids; FAD5 encodes a chloroplastic enzyme responsible for the synthesis of 16:1 fatty acids from galactolipids and sulpholipids in Arabidopsis ; FAD7 is a plastid-localized FAD involved in the synthesis of C16 and C18 polyunsaturated fatty acids in the prokaryotic glycerolipid pathway [ 38 ]. Expression of these three FADs shows an increase from GE to ME over the embryonic development in flax ( Figure 6 ), in agreement with the expression patterns of their homologs in Arabidopsis and some crops [ 17 , 19 , 39 ] and the gradual accumulation of the ALA and LA in flax seed. Characterizing the molecular functions of each FAD gene family member in flax might provide additional insights to improve the important flax oilseed products ALA and LA.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, we collected 144 seed coats RNA-seq data at different developmental stages of U’s Triangle six Brassica species [ 18 ]. Interestingly, co-DE R2R3-MYBs were found that 25 co-DE R2R3-MYBs in the groups UO and Torpedo of six Brassica species, but there was no co-differentially expressed R2R3-MYB gene in seed coats and leaves.…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the expression of BrNPFs among various tissues, publicly available RNAseq data from 59 different organs or tissues of B. rapa were retrieved from the NCBI database via the Bioproject accessions PRJNA185152, PRJNA778186, PRJNA641876, and PRJNA473318 [76][77][78][79]. Data were included from tissues comprising callus, stems, stem leaves, opened flowers, siliques, different developmental stages of heading leaves, floral buds, pistils, embryos, and seed coats.…”
Section: Expression Of Brnpfs Within Rna-seq Datamentioning
confidence: 99%